Developing Instructional Media Mobile Learning Based Android to Improve Learning Outcomes - Candra Irawan; Ery Tri Djatmika RWW (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2018)
This research aims to develop instructional media which is tested its feasibility and piloted in learning activities. The instructional media is developed using online builder Appypie with DCE developed-model. The product assessment is conducted by material expert, media expert and testing in a small and big group.The instrument of collected data is conducted by interviewing, questionnaire and test. The results of this research are: The instructional media product, mobile learning based android, has been using online builde Appypie, instructional media is feasible to apply after obtaining assessment result from material and media expert and users, The learning outcomes increases significantly between students with and without using instructional media. In summary, developed instructional media is feasible to app;y in a learning activity.